Change in a child's naevus prompts referral to a dermatology service - Cheng H; Oakley A; Rademaker M (CSIRO Publishing, 2014)
INTRODUCTION: Although melanoma is rare in children, parental concern about skin lesions often results in specialist referral and/or excision of benign lesions. AIM: To review dermatology referrals of children with skin lesions to determine reason for referral, macroscopic and dermatoscopic features of referred lesions, diagnosis, management and histology for excised lesions. METHODS: Referral letters, clinical and dermatoscopic images and outcomes were reviewed for skin lesions in children aged 0-18 years attending a teledermoscopy clinic over a 28-month period. RESULTS: Eighty-nine children with 128 lesions accounted for 9% of all referrals to the teledermoscopy clinic. The mean age of the children was 12 years (range 2-18 years). A 'changing mole' was the most common reason for referral (35 children; 39%), followed by 'possible melanoma' (19; 21%), and congenital naevus (9; 10%). The majority of lesions were benign melanocytic naevi (112 lesions; 88%). No lesions were diagnosed as melanoma or non-melanoma skin cancer. A history of change was given for 61/112 lesions (54%). Five lesions were excised; histopathological diagnoses were two spindle cell tumours of Reed, two compound naevi and one Spitz naevus. DISCUSSION: Change in a lesion, though a common trigger for referral, is less likely to indicate malignancy in children compared with adults and, as a sole criterion, does not necessitate specialist referral. Teledermoscopy clinics offer high quality macroscopic and dermatoscopic images and can assist in providing reassurance, where appropriate.